Analisa Pasal 412 Kuhp Baru Tentang Kohabitasi (Pendekatan Maqashid As-Syari’ah As-Syathibi Dan Teori Social Engineering Roscoe Pound) - Gusti Muslihuddin Sa’adi; Ahmadi Hasan; Masyithah Umar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract The phenomenon of cohabitation (kumpul kebo) has spreaded in the community, many couples live in the same house but do not have any marriage relations, especially among teenagers. This is very contrary to the norms that apply in society itself, the current shift in morality has triggered unrest among lawmakers, so that the cohabitation rule is included in Law No. 1 of 2023 concerning the Criminal Code (KUHP) article number 412. This research is a normative legal research, using qualitative literature research methods, the primary source used is Law No. 1 of 2023, and the sources include journals, books and scientific articles. This study aims to analyze article No. 412 of the new Criminal Code on cohabitation when viewed through the approach of Maqashid as-Shari'ah as-Syathibi and Roscoe Pound's social engineering theory. The results showed that article No. 412 on cohabitation in the new Criminal Code was in accordance with maqashid al-syariah hifz an-nasl, but was not included in dharuriyat, but included in the category of takmilat ad-dharuriyat, whose position was higher than al-hajiyat and at-tahsinaat. The prohibition of cohabitation is also an implementation of Roscoe Pound's legal theory of social engineering. The theory classifies the interests of society (public interest) precedence over private interests (private interest), so that cohabitation arrangements to maintain the morality and morals of the nation take precedence over individual freedom. Keywords: Cohabitation, Kumpul Kebo, Criminal Code, Maqashid as-Sharia, Roscoe Pound, Social Engineering Abstrak Fenomena kohabitasi (kumpul kebo) telah menjamur di masyarakat, banyak pasangan tinggal serumah namun tidak memiliki ikatan apapun, khususnya di kalangan remaja. Hal ini sangat bertentangan dengan norma yang berlaku di masyarakat sendiri, pergeseran moralitas yang terjadi saat ini memantik keresahan pembuat undang-undang, sehingga aturan kohabitasi dimasukkan ke dalam Undang-Undang No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana (KUHP) pasal 412. Penelitian ini merupakan penelitian hukum normatif, dengan menggunakan metode penelitian kualitatif kepustakaan, sumber primer yang digunakan adalah Undang-Undang No. 1 Tahun 2023, dan sumber skunder meliputi jurnal, buku dan artikel ilmiah. Penelitian ini bertujuan untuk menganalisa pasal 412 KUHP baru tentang kohabitasi jika ditinjau melalui pendekatan Maqashid as-Syari’ah as-Syathibi dan teori social engineering Roscoe Pound. Hasil penelitian menunjukkan pasal 412 tentang kohabitasi pada KUHP baru telah sesuai dengan maqashid al-syariah hifz an-nasl, namun tidak masuk ke dalam dharuriyat, tetapi masuk dalam katagori takmilat ad-dharuriyat, yang kedudukannya lebih tinggi dari al-hajiyat dan at-tahsinaat. Pelarangan kohabitasi juga merupakan implementasi dari teori hukum Roscoe Pound social engineering. Teori tesebut mengklasifikasikan kepentingan masyarakat (public interest) lebih didahulukan dari kepentingan pribadi (privat interest), sehingga pengaturan kohabitasi untuk menjaga moralitas dan akhlak bangsa lebih diutamakan dari pada kebebasan individual. Kata Kunci: Kohabitasi, Kumpul Kebo, KUHP Baru, Maqashid as-Syariah, Roscoe Pound, Social Engineering.